Beating yourself: How do runners improve their own records? - Foster, C.; de Koning, J. J.; Thiel, C.; Versteeg, B.; Boullosa, D. A.; Bok, D.; Porcari, J. P. (International Journal of Sports Physiology and Performance, 2020)
Background: Pacing studies suggest the distribution of effort for optimizing performance. Cross-sectional studies of 1-mile world records (WRs) suggest that WR progression includes a smaller coefficient of variation of velocity. Purpose: This study evaluates whether intraindividual pacing used by elite runners to break their own WR (1 mile, 5 km, and 10 km) is related to the evolution of pacing strategy. We provide supportive data from analysis in subelite runners. Methods: Men`s WR performances (with 400-m or 1-km splits) in 1 mile, 5 km, and 10 km were retrieved from the IAAF database (from 1924 to present). Data were analyzed relative to pacing pattern when a runner improved their own WR. Similar analyses are presented for 10-km performance in subelite runners before and after intensified training. Results: WR performance was improved in 1 mile (mean [SD]: 3:59.4 [11.2] to 3:57.2 [8.6]), 5 km (13:27 [0:33] to 13:21 [0:33]), and 10 km (28:35 [1:27] to 28:21 [1:21]). The average coefficient of variation did not change in the 1 mile (3.4% [1.8%] to 3.6% [1.6%]), 5 km (2.4% [0.9%] to 2.2% [0.8%]), or 10 km (1.4% [0.1%] to 1.5% [0.6%]) with improved WR. When velocity was normalized to the percentage mean velocity for each race, the pacing pattern was almost identical. Very similar patterns were observed in subelite runners in the 10 km. When time improved from 49:20 (5:30) to 45:56 (4:58), normalized velocity was similar, terminal RPE increased (8.4 [1.6] to 9.1 [0.8]), coefficient of variation was unchanged (4.4% [1.1%] to 4.8% [2.1%]), and VO2max increased (49.8 [7.4] to 55.3 [8.8] mLmin·kg). Conclusion: The results suggest that when runners break their own best performances, they employ the same pacing pattern, which is different from when WRs are improved in cross-sectional data.